Effect of climate change and variability-induced shocks and stresses on rural household livelihoods and their adaptation practices in West Arsi Zone, South-Central Ethiopia - Abebe Engda; Fantaw Yimer; Muluken Mekuyie; Menfese Tadesse (Climate Services)
This study aimed to evaluate the effects of climatic trends and variability on main livelihood practices (crop production), as well as farmers’ perceptions and adaptation to local climate change in West Arsi zone. The data gathered from 354 of the 364 sample households who took part in the survey in six Kebeles utilizing a standardized questionnaire served as the basis for this investigation. Ten surveys with incomplete responses were removed from the data analysis after the responses were reviewed for completeness across all questionnaire sections. Key informant interviews, focus groups, meteorological data from the Ethiopian Meteorological Institute, crop and aid beneficiary data from the West Arsi zone Bureau of Agriculture and Office for Disaster Risk Management were also used in the study. The Mann–Kendall statistical test was used to analyze climate trends. The descriptive and multivariate statistical models in SPSS v.25 and Ms Excel soft wares were used to analyze data. The results indicated significant increase in aggregated mean annual temperature (p < 0.001) by 0.045 °C per year and annual rainfall showed significant decrease (p < 0.1) by 3.7 mm per year in the study area, over the period 1983 to 2019. The results indicates annual rainfall was a significant predictor of crop production (t = 15.24, p < 0.05), and revealed a significant differences in household adaptation practices (p < 0.001) between agro ecological zones. The study also revealed that household demographic and socio-economic factors significantly influenced their adaptation choices, highlighting the need for further research on interventions that enhance local adaptation strategies.